Access to Research Findings from Mathematics Higher Education among Primary School Teachers - Samson S. Afolabi (West African Journal of Open and Flexible Learning, 2020)
Research is a main source of solutions to national development. Researches in Mathematics education are carried out in higher educational institutions of learning and educational research institutes. Making the end user to have access to research ﬁndings is crucial in research processes, of which many researchers do not extend their studies. This paper investigated the sources wherein the primary school Mathematics teachers access research ﬁndings. The study sampled 170 primary school Mathematics teachers from two purposively selected Local Government Areas of Ibadan municipalities in Nigeria. ARFQ was a research questionnaire in 2 sections with section A containing bio- data and section B has 10 items on a 3-point scale. The items were for the primary school Mathematics teachers to indicate the degree to which the listed items serve as a source of access to research ﬁndings to them. The instrument was validated by using 23 primary school Mathematics teachers outside the study sample, the coeﬃcient of reliability with Cronbach alpha was obtained as r= .70. A research question was answered and two hypotheses were tested item-by-item with t-test at .05 signiﬁcant level. The ﬁndings showed that female teachers quite very much outnumbered the male teachers in our primary schools. Books, discussions with colleagues and lecture room information are topmost as sources of their access to research ﬁndings. There is a signiﬁcant diﬀerence between male and female access to online materials (p=.026), conferences and workshops (p=.036) as sources of access to research ﬁndings in Mathematics education, with females having higher mean scores than males. There is a signiﬁcant diﬀerence between public and private school teachers' access to online materials (p=.003), journals and proceedings (p=.008) as sources of access to research ﬁndings in Mathematics education, with private schools having a greater mean. It was concluded that the teachers did not have access to the best sources of research outlets which are journals, proceedings, conferences and workshops. The study also recommended that journals and proceedings should be directed to primary school libraries.